Awareness of Information Resources and Services Among Persons With Disability in Public Liberareis of Kano State, Nigeria - Jamilu Abdullahi (IJoLIS, 2024)
Purpose: The study sought to determine the awarenes of information resources and serrvicxesa among persons with disability in public libraries in Kano State,Nigeria.